Effectiveness, implementation, and monitoring variables of intermittent hypoxic bicycle training in patients recovered from COVID-19: The AEROBICOVID study - Costa, Gabriel Peinado; Camacho-Cardenosa, Alba; Brazo-Sayavera, Javier; Viliod, Marcela Coffacci De Lima; Camacho-Cardenosa, Marta; Foresti, Yan Figueiredo; Carvalho, Carlos Dellavechia de; Merellano-Navarro, Eugenio; Papoti, Marcelo; Trapé, Átila Alexandre (Frontiers in Physiology, 2022)
Hypoxic exposure is safely associated with exercise for many pathological conditions, providing additional effects on health outcomes. COVID-19 is a new disease, so the physiological repercussions caused by exercise in affected patients and the safety of exposure to hypoxia in these conditions are still unknown. Due to the effects of the disease on the respiratory system and following the sequence of AEROBICOVID research work, this study aimed to evaluate the effectiveness, tolerance and acute safety of 24 bicycle training sessions performed under intermittent hypoxic conditions through analysis of peripheral oxyhemoglobin saturation (SpO2), heart rate (HR), rate of perceived exertion (RPE), blood lactate concentration ([La−]) and symptoms of acute mountain sickness in patients recovered from COVID-19. Participants were allocated to three training groups: the normoxia group (GN) remained in normoxia (inspired fraction of O2 (FiO2) of ∼20.9%, a city with 526 m altitude) for the entire session; the recovery hypoxia group (GHR) was exposed to hypoxia (FiO2 ∼13.5%, corresponding to 3,000 m altitude) all the time except during the effort; the hypoxia group (GH) trained in hypoxia (FiO2 ∼13.5%) throughout the session. The altitude simulation effectively reduced SpO2 mean with significant differences between groups GN, GHR, and GH, being 96.9(1.6), 95.1(3.1), and 87.7(6.5), respectively. Additionally, the proposed exercise and hypoxic stimulus was well-tolerated, since 93% of participants showed no or moderate acute mountain sickness symptoms; maintained nearly 80% of sets at target heart rate; and most frequently reporting session intensity as an RPE of “3” (moderate). The internal load calculation, analyzed through training impulse (TRIMP), calculated using HR [TRIMPHR = HR * training volume (min)] and RPE [TRIMPRPE = RPE * training volume (min)], showed no significant difference between groups. The current strategy effectively promoted the altitude simulation and monitoring variables, being well-tolerated and safely acute exposure, as the low Lake Louise scores and the stable HR, SpO2, and RPE values showed during the sessions.